2010
DOI: 10.1111/j.1365-313x.2010.04276.x
|View full text |Cite
|
Sign up to set email alerts
|

A DEAD box protein is required for formation of a hidden break in Arabidopsis chloroplast 23S rRNA

Abstract: SUMMARYIn plant chloroplasts, the ribosomal RNA (rRNA) of the large subunit of the ribosome undergoes postmaturation fragmentation processing. This processing consists of site-specific cleavage that generates gapped, discontinuous rRNA molecules. However, the molecular mechanism underlying introduction of the gap structure (the 'hidden break') is poorly understood. Here, we found that the DEAD box protein RH39 plays a key role in introduction of the hidden break into the 23S rRNA in Arabidopsis chloroplasts. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 58 publications
3
81
0
Order By: Relevance
“…Williams-Carrier, A. Vichas, G. Friso, A. Barkan, and K.J. van Wijk, unpublished data), and RH39 (Nishimura et al, 2010): the precise function of VDL is unknown, whereas both RH3 and RH39 are involved in rRNA maturation; RH3, in addition, promotes the splicing of some group II introns (Y. Asakura, E. Galarneau, K.P. Watkins, R.E.…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%
“…Williams-Carrier, A. Vichas, G. Friso, A. Barkan, and K.J. van Wijk, unpublished data), and RH39 (Nishimura et al, 2010): the precise function of VDL is unknown, whereas both RH3 and RH39 are involved in rRNA maturation; RH3, in addition, promotes the splicing of some group II introns (Y. Asakura, E. Galarneau, K.P. Watkins, R.E.…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%
“…5S and 5.8S rRNAs were detectable but not clearly separated. We analyzed 23S 300 rRNA by summation of the two previously described post-maturation fragments 23S´ and 301 23S´´ that result from hidden breaks of the mature 23S rRNA (Nishimura et al, 2010;Tiller 302 et al, 2012) Fragments 23S´ and 23S´´ were abundant in all analyzed samples. A third small 303 23S´´´ hidden break product and the potential full size rRNA precursor (Tiller et al, 2012) 304 were detectable only at very low intensity and disregarded in this study.…”
Section: Introductionmentioning
confidence: 99%
“…rRNA containing fractions were chosen for microfluidic 1046 electrophoresis (Salvo-Chirnside et al, 2011) and qualitative analysis of rRNA species (e.g. 1047 Figure 5, Supplemental Figure S3), with cytoplasmic 25S and 18S rRNA and chloroplast 23S 1048 and 16S rRNA annotations according to Nishimura et al (2010) and Tiller et al (2012). 1049…”
mentioning
confidence: 99%
“…Azpurua et al recently revealed that 28S rRNA of naked mole-rat, a subterranean rodent, is cleaved into two fragments within ES15L (D6) region; naked mole-rat cells have a 4-10-fold higher global translation fidelity relative to mouse cells, despite equivalent translation rates [30]. Additionally, the chloroplast ribosomes of an Arabidopsis thaliana nara12-1 mutant, which exhibits defective chloroplast 23S rRNA fragmentation processing, have dysfunctional translation elongation [31], thereby suggesting 28S/23S rRNA fragmentation is a translation control strategy in various organisms, regardless of its variable effects. Therefore, it is a leading hypothesis that the central hidden break involves splitting of 60S subunits in S. marmorata silk glands exposed to cold stress and, thus, diminished translation of Smsp-1 mRNA.…”
Section: Relationship Between Fragmented 28s Rrna and Translation Conmentioning
confidence: 99%
“…Besides the central hidden break, large subunit rRNA (28S/23S) fragmentation has been detected in various living cells and organelles [30][31][32][33][34][35][36][37][38][39]. Azpurua et al recently revealed that 28S rRNA of naked mole-rat, a subterranean rodent, is cleaved into two fragments within ES15L (D6) region; naked mole-rat cells have a 4-10-fold higher global translation fidelity relative to mouse cells, despite equivalent translation rates [30].…”
Section: Relationship Between Fragmented 28s Rrna and Translation Conmentioning
confidence: 99%